2002
DOI: 10.2337/diacare.25.10.1790
|View full text |Cite
|
Sign up to set email alerts
|

Components of the Metabolic Syndrome and Risk of Cardiovascular Disease and Diabetes in Beaver Dam

Abstract: OBJECTIVE—To determine whether components of the metabolic syndrome precede the 5-year incidence of cardiovascular disease and diabetes. RESEARCH DESIGN AND METHODS—A population of individuals aged 43–84 years was evaluated from 1988 to 1990 and again 5 years later. Medical history, blood pressure, and laboratory measures were obtained at both examinations following the same protocols. Subjects without diabetes were classified according to level of glycemia, high blood pressure, high-risk lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
260
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(278 citation statements)
references
References 25 publications
11
260
0
7
Order By: Relevance
“…13 Presence of metabolic syndrome amplifies the risk of developing type II diabetes mellitus 3-to 30-fold, depending on the criteria used. [14][15][16][17][18] In populations free of cardiovascular disease at baseline, cardiovascular morbidity and mortality increased 1.5-to 3-fold in the presence of metabolic syndrome 10,[19][20][21] and two-to fourfold in the presence of type II diabetes. 22 In spite of the use of different and modified definitions, the metabolic syndrome is associated with more extensive vascular damage and increased risk for subsequent events in patients with prevalent cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…13 Presence of metabolic syndrome amplifies the risk of developing type II diabetes mellitus 3-to 30-fold, depending on the criteria used. [14][15][16][17][18] In populations free of cardiovascular disease at baseline, cardiovascular morbidity and mortality increased 1.5-to 3-fold in the presence of metabolic syndrome 10,[19][20][21] and two-to fourfold in the presence of type II diabetes. 22 In spite of the use of different and modified definitions, the metabolic syndrome is associated with more extensive vascular damage and increased risk for subsequent events in patients with prevalent cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that metabolic syndrome is quite common, affecting 13.3 24.4% of Japanese men > = 30 years of age (3,4), and that it is a predictor of adverse cardiovascular events (5)(6)(7)(8). Several other metabolic disorders have also been associated with this syndrome, including microalbuminuria, and abnormalities in fibrinolysis and coagulation (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, risk is a progressive function and cannot simply be assumed as present or absent, depending on whether thresholds are exceeded or not. The fact that cardiovascular risk is a progressive function of several MS risk factors, and that the risk increases with increasing numbers of MS risk factors, 14,16 holds importance in continuous metabolic scoring such that cMetS, which considers all the components irrespective of any two or three combinations, thus attenuates the identification of early risk, especially in children.…”
Section: Introductionmentioning
confidence: 99%